"Let the music play" – experimental study on background music and time preference. Issue 4 (19th May 2022) - Israel, Avi; Rosenboim, Mosi; Shavit, Tal
ABSTRACT: Music plays a significant role in human life. The literature suggests that background music can influence an individual's decision-making process. Previous studies have shown that the tempo of music can affect people's choices about whether to prefer the present or the future when buying goods. We focused on the influence of the tempo of music on monetary time preference which is the willingness to wait for receiving money in the present compared to receiving it in a later period. In the experiment we asked participants to complete a questionnaire that included time delay questions to measure time preferences while listening to background music. Those who listened to music with a fast tempo were more likely to favour the present than those who listened to slow music or none at all. We suggest that this difference arises from an increase in people's cognitive load that leads to a status quo bias.